REDESAIN TAMAN WISATA ALAM PULAU BAKUT - Ilman, Ahmad Barkah; Heldiansyah, J.C (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Nature tourism park is a designation for landscapes that are protected through long-term planning, sustainable use and agriculture. These precious landscapes are preserved in their current state and promoted for tourism purposes. In the Bakut Island Nature Park, there are several groups of proboscis monkeys spread across the island, which are known as their natural habitat. Currently, the proboscis monkey, which is endemic to the island of Kalimantan, has received an endangered status after experiencing a population decline caused by the loss of the proboscis monkey's natural habitat. Currently, Bakut Island is one of the natural proboscis monkey conservation locations, but there is a natural tourism park that openly shows human activity at that location. This can affect the activity of proboscis monkeys in their survival. Responding to this, it is felt necessary to redesign the TWA which uses a concept that creates a relationship between humans and proboscis monkeys without directly involving the proboscis monkeys with the concept of Camouflage Architecture which hides human activity from the proboscis monkey's view and Biophilic Architecture in efforts to heal nature.